Ground Temperature Monitoring of a Cover Crop Variety Trial in Fairbanks, Alaska during 2024 Growing Season ... - Ward Jones, Melissa; Gannon, Glenna; Gasch, Caley (NSF Arctic Data Center, 2025)
The Permafrost Grown project (NSF RISE Award # 2126965) is co-producing knowledge with farmers in Alaska (Tanana Valley and Bethel) to investigate the interactions and feedbacks between permafrost and agriculture. Additional project objectives include understanding legacy effects over a 120-year cultivation history in the Tanana Valley, evaluating the socio-economic effects of permafrost-agriculture interactions and provide decision making tools for farmers and finally to utilize education and outreach activities to share knowledge with the farmers and the public. The project focuses on in-the-ground farming in a range of cultivation types including crops, peonies and livestock. The project is funded through NSF’s Navigating the New Arctic Initiative. This work was carried out at the University of Alaska Fairbanks Experimental Farm. This work was done through the Permafrost Grown Project as part of an effort to determine the thermal impact of a variety of cover crops and evaluate their potential impact on ...